2009
DOI: 10.4097/kjae.2009.57.2.210
|View full text |Cite
|
Sign up to set email alerts
|

Low dose ketamine reduces the induction of ERK1/2 and CREB signaling protein in a neuropathic pain model of rats

Abstract: Background: In addition to causing the loss of voluntary sensory and motor function, spinal cord injury (SCI) often creates a state of central neuropathic pain. Rats given SCI display increases in the activated form of transcription factors ERK 1/2 MAPK and CREB in the spinal cord, which correspond to allodynia in a model of neuropathic pain. This study was conducted to determine if low dose ketamine had an effect on the activation of ERK 1/2 and CREB in the development of neuropathic pain.Methods: This study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 28 publications
2
3
0
Order By: Relevance
“…In addition, ketamine restored the decreased p-ERK in the ACC of mice with comorbid neuropathic pain and depressive-like behaviors. These results are supported by recent evidences from pain field suggesting that ketamine's analgesic activity might be partly mediated through the modulation of several members of the MAPK pathways (Choi et al, 2009;Kwon et al, 2014;Mei et al, 2011). Specifically, it was shown that ketamine's analgesic effect is associated with an inhibition of both spinal astrocyte JNK activation (Mei et al, 2011) and the increased expression of p38 and phospho-p38 (Kwon et al, 2014) as well as with a decreased upregulated ERK (Choi et al, 2009) in the spinal cord of rats with neuropathic pain.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…In addition, ketamine restored the decreased p-ERK in the ACC of mice with comorbid neuropathic pain and depressive-like behaviors. These results are supported by recent evidences from pain field suggesting that ketamine's analgesic activity might be partly mediated through the modulation of several members of the MAPK pathways (Choi et al, 2009;Kwon et al, 2014;Mei et al, 2011). Specifically, it was shown that ketamine's analgesic effect is associated with an inhibition of both spinal astrocyte JNK activation (Mei et al, 2011) and the increased expression of p38 and phospho-p38 (Kwon et al, 2014) as well as with a decreased upregulated ERK (Choi et al, 2009) in the spinal cord of rats with neuropathic pain.…”
Section: Discussionsupporting
confidence: 79%
“…These results are supported by recent evidences from pain field suggesting that ketamine's analgesic activity might be partly mediated through the modulation of several members of the MAPK pathways (Choi et al, 2009;Kwon et al, 2014;Mei et al, 2011). Specifically, it was shown that ketamine's analgesic effect is associated with an inhibition of both spinal astrocyte JNK activation (Mei et al, 2011) and the increased expression of p38 and phospho-p38 (Kwon et al, 2014) as well as with a decreased upregulated ERK (Choi et al, 2009) in the spinal cord of rats with neuropathic pain. In accordance with these findings, it has been shown that a single dose of subanesthetic ketamine which recruits the MAPK signaling cascade (Kohtala et al, 2019;Li et al, 2010) also ameliorates chronic stress-induced deficits in spine number and function (Li et al, 2011), a common characteristic in depression (Banasr et al, 2011).…”
Section: Discussionsupporting
confidence: 79%
“…The NMDA receptor is an excitatory amino acid (EAA) receptor, and NMDA receptor antagonists have been shown to exert a neuroprotective effect in central nervous system ischemia [ 17 ]. Furthermore, elevated EEAs lead to the activation of several MAPKs, including ERK 1/2, JNK, and p38 [ 18 , 19 ]. The key element in this process is the glutamate receptor that increases in number at neural junctions by phosphorylation, elevating the reactivity to glutamate, an excitatory neurotransmitter [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Analgesic drugs, such as dexmetomidine, type-2 cannabinoid receptor agonists, and ketamine alleviate neuropathic pain by restraining MAPK activation in the spinal cord. [70][71][72] In dorsal horn neurons, MAPK phosphorylates and inhibits K v 4.2 channels, which mediate type-A potassium currents and are involved in pain plasticity. [73][74][75] It is possible that NAC treatment in diabetic mice enhances the activity of K v 4.2 channels, therefore reducing excitability of secondary order neurons in the dorsal horns of the spinal cord.…”
Section: Discussionmentioning
confidence: 99%